Integrating datasets to dissect NFYC-AS1 RNA- and transcription-dependent functions: comparative transcriptome profiling of knockdown strategiesGene Expression Omnibus GEO - Giulia Pagani; Cecilia Pandini; Martina Tassinari; Paolo Gandellini (Data in Brief)
The recent discovery of antisense RNAs (asRNAs) as key regulators of biological processes has highlighted the need to challenge their mechanism(s) of action using complementary approaches. Indeed, asRNAs can act in cis on their sense gene or in trans on distally located targets, by exploiting either transcription- or RNA-dependent mechanisms. Here we present a comparative transcriptome profiling of cancer cells knocked-down for the asRNA NFYC-AS1 with two different approaches: i) Gapmer Antisense Oligonucleotides to assess RNA-dependent mechanisms, and ii) CRISPR/Cas9 deletion of the transcription start site to study transcription-dependent mechanisms. We describe in detail the strategies used to silence the asRNA and evaluate the consequences at the transcriptome level by RNA-sequencing. Moreover, we outline the analyses conducted to correctly manage the variability across replicates and the off-target effects of either method. The integration of the obtained datasets revealed commonalities and divergencies of the two approaches, which was fundamental for dissecting NFYC-AS1 function. The information reported here can help researchers to reuse the data described in the datasets. Finally, the comparative workflow can be potentially applied to the functional study of any asRNA of interest.